Method for the preparation of hybrid nanostructured composites containing cellulose nanoparticles and metal compound nanoparticles - Patent Application 20070233334
Patent Information
- Application Number
- JP2023553321
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-02
- Filing Date
- 2022-02-25
- Publication Date
- 2025-03-05
AI Technical Summary
Existing methods for producing hybrid composites of cellulose nanoparticles and metal compound nanoparticles are complex, costly, and environmentally unfriendly, often leading to poor yield and quality of the composite due to degradation and non-homogeneous mixing at the nanoscale.
A method involving the use of a molten metal salt solvent to dissolve cellulose, followed by the addition of a precipitation reactant and an antisolvent to precipitate cellulose nanoparticles, while simultaneously forming metal compound nanoparticles, resulting in a homogeneous hybrid nanostructured composite.
The method produces highly homogeneous hybrid nanostructured composites with improved properties, reducing complexity, cost, and environmental impact, and achieving better mixing and stability of the nanoparticles.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
2. Background of the Invention
[0001] 1. Field of the invention The present invention relates to a method for the preparation of a hybrid nanostructured composite comprising cellulose nanoparticles and metal compound nanoparticles, to a nanostructured composite product obtainable by the method, and to uses thereof. 2. Description of Related Technology
[0002] The production of cellulose nanoparticles is known in the art. For example, Delgado-Aguilar et al., in BioResources 10(3), 5345-5355 (2015), describe several methods for preparing cellulose nanofibers from cellulose-containing raw materials, including a combination of chemical pretreatment and high-energy mechanical treatment. These methods use costly and non-environmental chemicals and / or solvents, have high energy consumption, and have several complicated processing steps.
[0002]
[0003] Known simplified routes for producing cellulose nanoparticles use acidic solvents (H2SO4, HCl and / or SO2 in water or organic solvents), but the yield and quality of the resulting cellulose nanoparticle products are poor because cellulose is decomposed into sugars and other compounds, thereby reducing the applicability of the resulting products.
[0003]
[0004] WO2017 / 055407 describes dissolving cellulose in a substantially proton-free inorganic molten salt solvent medium, preferably ZnCl2 hydrate, and precipitating the cellulose with a poor solvent into high aspect ratio nanocellulose fibrils. However, the properties of the resulting cellulose nanocrystals are not as good as desired in terms of product purity, crystallinity, chemical stability and mechanical properties.
[0004]
[0005] WO2020212616 describes a further improved method for preparing micro- or nanocrystalline cellulose from virgin cellulose, which comprises contacting the cellulose with a first solvent containing 40-65 wt. % ZnCl2 in water, thereby dissolving the amorphous cellulose phase preferentially over the crystalline cellulose phase to produce cellulose microparticles with a high yield and high degree of crystallinity having an XRDI-type structure, and then contacting the resulting product with a second solvent, preferably containing 65-90 wt. % ZnCl2 in water at a higher concentration than the first solvent, to produce cellulose nanoparticles with an XRDI-type structure in high yield, high degree of crystallinity and high purity.
[0005]
[0006] The production of nanoparticles of metal compounds is also well known. However, the problem is to form a nanostructured composite in which both the nanoparticles of metal compounds and the nanoparticles of cellulose are homogeneously mixed at the nanoscale. The nanoparticles usually have a size of about 1 to less than 100 nm, preferably less than 60 nm or 40 nm, and most preferably even less than 20 nm. In the case of cellulose nanocrystals, which have a large aspect ratio, this is not the size range of the length dimension, but the smaller thickness dimension. Since the nanostructured composite is a composite in which the nanoparticles are homogeneously dispersed at the nanoscale, most of the cellulose nanoparticles and the adjacent metal compound nanoparticles are within the above nanoscale dimensions that can be established by scanning electron microscopy (SEM).
[0006]
[0007] Direct mixing of metal nanoparticles with nanocellulose particles is not a complicated process, but it does require a lot of mechanical energy, which can also cause damage and / or degradation of the cellulose nanoparticles, but in many cases the problem is that the product is not homogeneously mixed at the nanoscale.
[0007]
[0008] WO2019229030A1 describes a method for the preparation of hybrid inorganic-organic materials, but this method does not result in a nanostructured composite containing nanoparticles of metal compounds and cellulose. The method involves forming a solution of cellulose in an ionic liquid solvent, dispersing an inorganic material, such as alumina or silica, in the cellulose solution, and adding an antisolvent to precipitate nanocellulose together with the dispersed inorganic material. The resulting co-precipitated inorganic particles are not nanoparticles, in contrast to the inorganic particles of the present invention, and the hybrid composite is not a nanostructured composite. Alumina (Al2O3) dispersed in ZnCl2 together with NC-ZnCl2 results in alumina particles with an average particle size of 100 nm or more that are not nanoparticles.
[0008]
[0009] Farooq ea describes hybrid composites containing cellulose nanoparticles modified with metal nanoparticles, especially zinc oxide nanoparticles, in International Journal of Biological Macromolecules 154, (2020) 1050-1073. Farooq describes several preparation methods for producing cellulose nanoparticles in chapter 2 of his review, including alkaline acid treatment of cellulosic biomass to produce cellulose nanoparticles, or enzymatic pretreatment, or pretreatment with ionic liquids, followed by hydrolysis and high-pressure homogenization or mechanical treatment. Farooq also describes various methods for the preparation of metal nanoparticles in chapter 3 of his review, where different morphologies are obtained by different known methods. For example, it is described to produce zinc oxide nanoparticles by a non-hydrolytic (solution) method using zinc acetate dehydrate. Farooq further describes various different methods of preparing hybrid composites in chapter 3.3, including simply mixing cellulose nanoparticles and metal oxide nanoparticles in aqueous suspension without the use of an external reducing agent, mixing cellulose nanoparticles and metal nanoparticles with a reducing agent, or surface modification of cellulose nanoparticles and adding metal oxide nanoparticles. All preparation methods start with an aqueous suspension of cellulose nanoparticles.
[0009]
[0010] Ma et al. in Cellulose (2016) 23:3703-3715 describe a method for the preparation of ZnO-cellulose nanocomposites, which involves mixing a cellulose-zinc chloride (ZnCl2) aqueous solution with a cellulose-NaOH / urea aqueous solution in a colloid mill at room temperature. Cellulose is completely soluble in a 65 wt% ZnCl2 solution at 80 °C, and cellulose in NaOH / urea aqueous solution is also completely soluble. When the solutions are mixed, large aggregated ZnO grains are formed by the reaction of ZnCl2 with hydroxide in the presence of dissolved cellulose in an amount of 0.5 wt% to 2 wt%. The presence of cellulose in the ZnO precipitation is to prevent the growth and aggregation of ZnO particles. The reaction mixture was ground into nano-sized grains in a colloid mill, and the resulting ZnO-cellulose nanocomposite was calcined at 575 °C to produce nano-ZnO particles. XRD measurements showed no crystallinity peaks of cellulose, indicating the absence of nanocellulose crystals in the obtained product after calcination. The drawback of the method is that it involves a high-energy grinding step, which is more complicated and costly, but more importantly leads to degradation and discoloration of the cellulose present. The resulting nanocomposite is called ZnO-cellulose, but contains only ZnO nanoparticles and no nanocellulose crystals. The product has a yellow-orange emission band. The resulting nanoparticles are not suitable as a replacement for white pigments.
[0010]
[0011] Ruszala et al., IJCEA, vol. 6, no. 5, October 2015, 331-340, describes various alternative materials to replace TiO2 as a white pigment in paints, and in part VA1, ZnO is also described, but ZnO nanoparticles are not described. It is noted that ZnO is not often used in paints due to its lack of stability and low refractive index. Ruszala does not describe cellulose nanoparticles or cellulose-ZnO hybrid nanoparticles.
[0011]
[0012] The disadvantage of the described methods for the preparation of hybrid composites is that they are complex, involve multiple process steps and consume expensive chemicals, making them economically and environmentally unattractive.
[0012]
[0013] It is therefore an object of the present invention to provide a method for the preparation of a hybrid composite comprising metal nanoparticles and cellulose nanoparticles, which is less complicated and leads to a highly homogeneous hybrid nanostructured composite in which the metal nanoparticles and the cellulose nanoparticles are homogeneously mixed at the nanoscale. The method of the present invention preferably has at least one of the following advantages: fewer process steps, cheaper chemicals, lower processing costs, lower energy consumption, and lower environmental impact. Summary of the Invention
[0013]
[0014] According to the present invention, there is provided a method for preparing a hybrid nanostructured composite material comprising cellulose nanoparticles and metal compound nanoparticles, comprising the steps of: a) contacting virgin cellulose with a molten metal salt solvent M1-S containing a metal ion M1 to dissolve the virgin cellulose; b) Add a precipitation reactant B to convert at least a portion of the metal ions M1 in the molten metal salt solvent M1-S into metal compound nanoparticles M 1- X or by contacting with a solution of a salt containing metal ions M2, at least a portion of the metal ions M1 is exchanged with metal ions M2 to obtain a metal compound M 2- precipitating the X nanoparticles, either directly or by adding a precipitating reactant B; c) adding an anti-solvent before, during or after step b) to precipitate the cellulose nanoparticles; d) isolating the co-precipitated cellulose and metal compound nanoparticles to obtain a hybrid nanostructured composite; e) optionally converting the metal compound in the hybrid nanostructured composite to another metal compound. At least one of the mentioned disadvantages has been overcome by providing a method comprising:
[0014]
[0015] In another aspect, the present invention relates to a hybrid nanostructured composite material comprising metal nanoparticles and cellulose nanoparticles obtainable by the method of the present invention, having improved homogeneity and improved in-use properties.
[0015]
[0016] Yet another aspect of the present invention relates to the use of hybrid nanostructured composites in food packaging, biopharmaceutical, biomedical, cosmetic and electronics applications such as solar cells, flexible displays, ultracapacitors etc., where nanoparticles of metal compounds including metals, e.g. Li, Mn, Ti, Zn, Ru etc. are combined with nanocellulose papers, foils, sheets, tapes etc.
[0016]
[0017] Yet another aspect of the present invention relates to the use of metal nanoparticles, or cellulose nanoparticles, or most preferably the use of the hybrid nanostructured composite of the present invention, as white base pigments, such as but not limited to paints, coatings, adhesives, sealants, inks, plastics, but also in cosmetics, such as toothpaste, or in foods. The mentioned uses are particularly related to replacing titanium compounds, such as titanium dioxide (TiO2), as white pigments in the mentioned applications. Although nanocellulose is white and ZnO itself is also known to be white, it has been surprisingly found that the hybrid nanostructured composite of the present invention is even whiter than the constituent nanoparticles themselves, probably because ZnO is very well dispersed in the nanocellulose.
[0017]
[0018] The features and advantages of the present invention may be understood with reference to the following drawings. [Brief description of the drawings]
[0018] [Figure 1]
[0019] Example A is a schematic diagram of one embodiment of the method of the present invention showing general process steps in the preparation of a hybrid composite of cellulose nanocrystals and metal compound nanoparticles, NCs-M1OH. [Diagram 2]
[0020] Example A1 is a specific embodiment of the method of Example A, showing the use of ZnCl.4H0 as a molten salt solvent to prepare NCs-Zn(OH) hybrid complex. [Diagram 3]
[0021] Example B is a general schematic diagram of another embodiment of the method of the present invention for producing NCs-M1HCO3 hybrid complexes. [Figure 4]
[0022] Example B1 is a specific embodiment of Example B, which is a method for preparing NCs-Zn(HCO3)2 hybrid composite. [Diagram 5]
[0023] Example C is a general schematic diagram of another embodiment of the method of the present invention for producing NCs-M2-acetate hybrid complexes. [Figure 6]
[0024] Example C1 is a schematic illustration of one embodiment of the inventive method of Example C for producing NCs-Li-acetate hybrid composites. Detailed Description of Certain Embodiments of the Invention
[0019]
[0025] The following is a description of certain embodiments of the present invention, given by way of example only and with reference to the drawings. Referring to Example A in FIG. 1, solid virgin cellulose (or virgin cellulose-containing feedstock) C s FIG. 2 shows an embodiment of the method of the present invention in which the solid virgin cellulose C is contacted with a molten metal salt solvent M1-S, where M1 is a metal. Example A1 in FIG. 2 shows a preferred embodiment in which the molten metal salt solvent M1-S is ZnCl2.4H2O, where M1 is zinc. In this first step, the solid virgin cellulose C is s is dissolved and a suspension or solution of nanocellulose dissolved in molten metal salts (NC d -M1-S, preferably NC d -ZnCl2) is formed. It should be noted that the terms suspension and solution are used interchangeably for the product obtained from the dissolution process since the product obtained from the dissolution step contains cellulose in nanocrystalline form and may also contain molecularly dissolved cellulose polymers, oligomers or monomers.
[0020]
[0026] The cellulose particles obtained in this first step may be cellulose particles having XRDI or XRDII structure. However, it is preferred that the cellulose particles obtained are exfoliated cellulose nanoparticles having XRDII structure before the metal precipitating agent is added, since this leads to nanocellulose with a higher aspect ratio and hybrid composites in which cellulose and metal compound nanoparticles are more homogeneously mixed at the nanoscale.
[0021]
[0027] In a preferred embodiment, the cellulose particles obtained in the first step are cellulose particles with XRDI type structure which are converted in a separate second step into cellulose nanoparticles with XRDII type structure, preferably before the addition of the metal precipitating agent, as explained above.
[0022]
[0028] Next, the resulting cellulose solution NC d -Adding a precipitating reagent to M1-S converts at least a portion of the molten metal salt solvent M1-S into insoluble metal compounds M1-X that precipitate as nanoparticles in the molten metal salt. In the embodiment shown in Figures 1 and 2, the metal precipitating reagent is NaOH and the metal nanoparticles formed are metal hydroxide M1-OH nanoparticles. In a preferred embodiment of Example A1 in Figure 2, the resulting solution contains dissolved nanocellulose NCs in ZnCl2.4H2O molten metal salt. d and Zn(OH)2 nanoparticles.
[0023]
[0029] The addition of metal precipitating agents may also decrease the solvent quality of the molten salt solvent. d The NCs started to form a cloudy gel with the precipitated metal compound M1-OH (Zn(OH)2, example A1) and only after the addition of the antisolvent, d A clear phase separation was observed to occur between the -M1-OH cogel and the molten salt solvent.
[0024]
[0030] In the next step, anti-solvent C (HO in Examples A and A1) is added to reduce the solvent power of the molten metal salt and form cellulose nanoparticles NCs. s is precipitated with M1-OH nanoparticles (preferably. The precipitate is then separated to obtain the solid hybrid composite product NC s -Zn(OH)2 is obtained. The separation step may include filtration and / or centrifugation and may include one or more washing and / or drying steps. The method includes steps a) to d) as a continuous process without an intermediate step to reduce particle size. In particular, the method does not include and does not need to include a grinding, milling, sonication step to reduce particle size.
[0025]
[0031] Preferably, the method also includes a recycling step for regenerating the molten metal salt solvent M1-S, which step includes concentrating the dilute molten salt for reuse in the first step. The poor solvent is preferably water, since the metal salt solvent M1-S can be regenerated from the dilute solvent separated simply by evaporating the water to the concentration of the molten salt desired in the cellulose dissolution step.
[0026]
[0032] Examples A and A1 in Figures 1 and 2 show an embodiment in which a metal precipitating agent is added followed by an anti-solvent to precipitate the nanocellulose. Examples B and B1 in Figures 3 and 4 show an alternative embodiment of the method of the invention in which an anti-solvent is added to precipitate the nanocellulose followed by the metal precipitating agent.
[0027]
[0033] First, solid virgin cellulose (raw material) C S is contacted with a molten metal salt solvent M1-S, preferably in the same manner as described above for Example A, to form a molten metal salt NC d A solution of cellulose nanoparticles of XRD II type in M1-S is then produced. An anti-solvent C, preferably water, is then added to precipitate nanocellulose NCs with a size typically less than 200 nm, to which the metal M1-S (preferably ZnCl2) is attached in molecular form. s Generate.
[0028]
[0034] In the next step, a metal precipitating agent is added to form the molten metal salt solvent M 1- S is converted into a metal compound M1-X, which is precipitated as nanoparticles onto the precipitated nanocellulose particles, forming a highly homogeneous hybrid complex of the metal compound and the cellulose nanoparticles. In examples B and B1, the metal precipitating reactant is KHCO3, and the hybrid complex is formed by the cellulose nanoparticles NC s and nanoparticles of a modified metal compound M1HCO3; preferably the hybrid complex NC shown in Example B1. s -Zn(HCO3)2.
[0029]
[0035] Examples C and C1 in Figures 5 and 6 show a variation of Examples B and B1 in which the metal precipitating reactant includes a metal cation M2 different from the metal M1 in the molten metal solvent. In this embodiment, the metal M1 of the molten metal solvent is at least partially exchanged with the metal cation M2. Nanoparticles of the metal M2 compound are then formed into the precipitated cellulose nanoparticles NC. s In Example C, the metal precipitating reactant is M2-acetate, and the hybrid complex formed is a mixture of M2-acetate and cellulose nanoparticles NCs. s Example C1 shows a specific embodiment of a method for forming a hybrid composite comprising Li-acetate and cellulose nanoparticles using a Li-acetate precipitating reagent. This hybrid composite is useful, for example, in solar cells. When the precipitating reagent water is added to a ZnCl2.nH2O molten salt cellulose solution, the cellulose precipitates with much of the ZnCl2 remaining in the precipitate. The precipitate is then washed with water to remove or reduce the amount of ZnCl2 (as is typically done), or with another metal salt M2-X to replace the ZnCl2. Detailed Description of the Invention
[0030]
[0036] The present invention relates to a method for preparing a hybrid nanostructured composite comprising cellulose nanoparticles and metal compound nanoparticles, a nanostructured composite product obtainable by the method, and uses thereof. The method includes the steps of contacting virgin cellulose with a molten metal salt solvent M1-S to dissolve the virgin cellulose, optionally exchanging at least a portion of the metal ions M1 with metal ions M2 to convert at least a portion of the metal ions M1 and / or optional M2 into metal compound nanoparticles, precipitating the cellulose nanoparticles, and isolating the co-precipitated cellulose and metal compound nanoparticles.
[0031]
[0037] The metal compound can be precipitated before or after the precipitation of the cellulose nanoparticles. In a preferred embodiment, the metal compound particles are precipitated after the precipitation of the cellulose nanoparticles. The precipitation of the cellulose nanoparticles forms a kind of gel-like precipitate with a high amount of metal ions M1 of the molten salt metal compound. Preferably, the amount of M1 metal in the precipitate is reduced, preferably by filtration and washing, to the amount required in view of the desired amount of metal compound nanoparticles on the cellulose nanoparticles, and then the metal compound nanoparticles M1-X are precipitated on the nanocellulose. If a different metal M2 is desired in the metal compound in view of the envisaged application of the hybrid composite, the metal M2 ion can be added to the molten salt and precipitated together with or instead of the metal M1 compound. However, preferably, the metal ion M2 is not present in the molten salt and after the cellulose is initially precipitated, the molten M1 metal salt solvent is separated from the precipitated nanocellulose for recycling and reuse in the first step, and then the precipitated nanocellulose, which remains wet with the molten metal M1 salt solvent, is contacted with a metal M2 salt in one or more steps to exchange the metal M1 of the molten salt solvent for metal M2, after which metal M2 compound nanoparticles are precipitated, optionally washed and then dried.
[0032]
[0038] The method according to the present invention comprises, as a first step, a) contacting virgin cellulose with a molten metal salt solvent M1-S containing a metal ion M1 to dissolve the virgin cellulose. The molten metal salt M1-S is preferably a zinc halide, more preferably zinc chloride, zinc bromide or a hydrate thereof, even more preferably ZnCl2.4H2O. The advantage of the molten metal salt ZnCl2 hydrate, preferably ZnCl2.4H2O, is that cellulose is sufficiently dissolved with little decomposition, especially in a molten salt that does not contain protons and preferably contains a proton scavenger, and depolymerization of cellulose is reduced.
[0033]
[0039] In one embodiment, the molten metal M1 salt solvent comprises a metal cation M2 other than the metal M1 of the molten salt solvent, preferably ZnCl2, and a M2 metal chloride, the metal cation M2 being preferably one or more selected from the group Li, Mn, Ti, Zn, Nd, Cd, Ag and Ru, most preferably TiCl2, MnCl2, LiCl2, and preferably the amount of M2 metal is less than 20%, preferably less than 10 or 5 mol% of the amount of M1.
[0034]
[0040] Nanoparticles of cellulose XRDII type nanoparticles can be prepared by the method described in WO2017 / 055407. However, a preferred method for preparing cellulose XRDII type nanoparticles is described in WO2020212616. In this preferred embodiment, the method of the present invention comprises in step a) contacting virgin cellulose with a first solvent, characterized in that the first solvent is an aqueous solution containing 40 to 65% by weight of ZnCl2 in water, thereby dissolving the amorphous cellulose phase preferentially over the crystalline cellulose phase in step b), and c) optionally isolating the obtained crystalline cellulose having an XRDI type structure. Then, in step d), which comprises contacting the optionally separated crystalline cellulose having an XRDI type structure with a second solvent containing 65 to 90% by weight of ZnCl2 in water at a higher concentration than the first solvent, cellulose having an XRDII type structure is prepared, where the second solvent and preferably the first solvent also do not contain a protonic acid, and preferably contain a proton scavenger. In this method, crystalline cellulose nanoparticles having an XRDII structure can be obtained in high yield, high crystallinity and high purity (i.e. small amounts of saccharide oligomers or monomers and their degradation products). In this method, it is preferred that the temperature of steps a) and b), preferably also step d), is below 80°C, preferably below 70, 60 or even 50°C. It is also possible to carry out the method at room temperature. Lower temperatures present milder conditions and increase the preference for dissolving only the amorphous phase, but also increase the time required for completion. Typically, a higher concentration of ZnCl2 is preferably combined with a lower temperature, or vice versa, a lower concentration of ZnCl2 may be combined with a higher temperature. Alternatively, it may be preferred to carry out the contact step A at a higher temperature, for example between 50 and 80°C, followed by quenching after a predefined optimal contact time to prevent further dissolution of the crystalline cellulose. Quenching means a quick reduction in temperature and / or a quick dilution with water.
[0035]
[0041] In the method according to the present invention, as step b), a precipitating agent B is added to convert at least a part of the metal ions M1 of the molten metal salt solvent M1-S into metal compound nanoparticles M 1- X or by contacting with a solution of a salt containing metal ions M2, at least a portion of the metal ions M1 is exchanged with metal ions M2 to obtain a metal compound M 2- The method comprises precipitating X nanoparticles, either directly or by adding a precipitating reactant B.
[0036]
[0042] The precipitating agent B is preferably a base anion X, preferably comprising hydroxy, carbonate or carboxylate, which forms nanoparticle precipitates M1-X with metal M1 and / or M2-X with metal M2. The precipitating agent B is preferably added as a salt comprising a base anion and hydrogen or a group IA metal cation, preferably sodium or potassium. The precipitating agent B is selected from the group NaOH, KOH, KHCO3, formate or acetate. The metal compound nanoparticles formed are, for example, M1-OH, M1-HCO3, M1-HCOO. - or nanoparticles of M1-CH3COO.
[0037]
[0043] In another embodiment, the precipitating reagent B comprises a metal ion M2 other than the metal M1 or exchanges the metal M1 with the metal M2 to form a precipitate of a metal M2-X, where the metal cation M2 is preferably one or more selected from the group of Li, Mn, Ti, Nd, Cd, Ag and Ru.
[0038]
[0044] The method according to the invention comprises, as step c), the addition of an anti-solvent before, during or after step b) to precipitate the cellulose nanoparticles. Preferably, the anti-solvent C is water, a ketone or an alcohol, preferably water added in an amount to reduce the salt concentration of the molten salt, preferably the ZnCl2 concentration, to 10-30 wt.%, preferably 15-25 wt.%. In step d), the resulting coprecipitated cellulose and metal compound nanoparticles are isolated, preferably by filtration and / or centrifugation, optionally washed and dried to obtain a hybrid nanostructured composite.
[0039]
[0045] It should be noted that WO2019229030A1 describes the co-precipitation of cellulose with pre-dispersed inorganic particles. This differs from the present method of converting the metal of the molten metal salt to form nanoparticles on the nanocellulose crystals, which, in contrast to the prior art, achieves inorganic compound particles with a significantly smaller size of less than 70 nm, preferably less than 50 nm, more preferably less than 30 nm, and most preferably even less than 20 nm. Another drawback of WO2019229030A1 is that it only works with certain metal oxides that can be dispersed in the molten salt solvent ZnCl2. This is not possible, for example, with oxides of "heavier" metals, such as ZnO, NdO, rare earth oxides, etc.
[0040]
[0046] In one embodiment of the method of the present invention, in step b), a precipitating agent B is added to convert at least a portion of the metal ions M1 into a metal compound M 1- X nanoparticles, and then in step c) an anti-solvent C is added to form the metal compound M 1- The cellulose nanoparticles are precipitated in the presence of nanoparticles of X, optionally followed by one or more steps of filtering, washing and drying.
[0041]
[0047] In one embodiment of the method of the invention, step a) is followed by step c) and then step b) which comprises adding an anti-solvent C to the cellulose solution obtained in step a) to form a gel of precipitated cellulose nanoparticles, optionally followed by separating and washing the gel to reduce the concentration of the metal salt in the molten salt solvent, followed in step b) by adding a precipitating reactant B to convert at least a portion of the metal ions M1 into metal compounds M in the presence of the cellulose nanoparticles. 1- Convert into X nanoparticles.
[0042]
[0048] In a particular embodiment of this method, the molten metal salt solvent is preferably ZnCl2.4H2O and the precipitating reactant B is a hydroxide base, preferably added as sodium hydroxide, resulting in a hybrid composite of cellulose and zinc hydroxide nanoparticles. Optionally, the resulting hybrid composite is then treated to convert the zinc hydroxide nanoparticles to zinc oxide nanoparticles by drying at elevated temperatures, preferably between 70-350°C, preferably between 80-300°C, and even more preferably between 80-280°C.
[0043]
[0049] In an alternative embodiment of the method of the invention, step a) is followed by step c) of adding an anti-solvent C to the cellulose solution obtained in step a) to form a gel of precipitated cellulose nanoparticles, optionally followed by step b) of separating and washing the gel to reduce the concentration of the metal salt in the molten salt solvent, and then exchanging at least a portion of the metal ions M1 with metal ions M2 by contacting the solution with a solution of a salt containing the metal ions M2, with or after the addition of a precipitating reactant B, the metal compound nanoparticles M 2- A precipitate of X forms.
[0044]
[0050] The precipitating reagent B and anti-solvent C can be added separately as described above, but can also be added together in a single combined step c) and d). Alternatively, a single compound is added that acts as both precipitating reagent B and anti-solvent C to simultaneously precipitate both metal compound nanoparticles and cellulose nanoparticles. For example, precipitating reagent B affects the solubility of dissolved cellulose to such an extent that it converts the metal M1 of the molten salt into a precipitate, thereby precipitating cellulose. Precipitating reagent B can be added as a solution of a salt, e.g., NaOH, in water, to precipitate both the metal hydroxide compound and cellulose.
[0045]
[0051] The method according to the invention optionally comprises, as step e), converting the metal compounds in the hybrid nanostructured composite to another metal compound. This can be done, for example, by pyrolysis, ion exchange, reduction or oxidation. Preferably, the metal compounds in the hybrid nanostructured composite comprise hydroxides, carbonates or carboxylates or combinations thereof, preferably carbonate hydroxide compounds, which are optionally converted to metal oxides by pyrolysis, preferably under vacuum.
[0046]
[0052] Optionally, in order to link the cellulose nanoparticles, interconnecting agents are added in the method, which are preferably selected from the group of glycerol, citric acid, acetate or chitosan, preferably organometallic compounds of the exchanged metal M2, preferably M2-acetate or -citrate, which interconnecting agents are preferably added in step b) or c).
[0047]
[0053] The present invention also relates to a hybrid nanostructured composite comprising cellulose nanoparticles and metal compound nanoparticles obtainable by the method according to the present invention, preferably comprising 2-20% by weight of metal compound relative to the total dry weight of the nanostructured composite. The hybrid nanostructured composite preferably comprises cellulose nanoparticles having an X-ray diffraction (XRD) type II structure, preferably with an aspect ratio AR of at least 5, preferably at least 10, preferably with a minimum size of less than 60 nm, preferably less than 40 nm, more preferably less than 30 nm, and metal compound nanoparticles having an average particle size of less than 80 nm, preferably less than 60 nm, more preferably less than 40 nm, wherein the cellulose and metal compound nanoparticles are homogeneously mixed on the nanoscale. A preferred hybrid nanostructured composite of the present invention comprises, as metal compound, zinc chloride, zinc hydroxide, zinc oxide or zinc carbonate, lanthanum chloride, lanthanum hydroxide, lanthanum oxide or lanthanum carbonate, or lithium acetate.
[0048]
[0054] The invention also relates to the use of the hybrid nanostructured composites of the invention for energy generation, in electronic devices, as pigments and / or pigment supports, as whitening agents or fillers in food or personal care products, as antimicrobial compounds, in antimicrobial clothing, in flexible, optically clear papers, foils, tapes or fabrics.
[0049]
[0055] Nanocellulose-based hybrid nanomaterials have great potential applications in food packaging, biopharmaceuticals, biomedicine, cosmetics and electronics. Hybrid composites combine the properties of functional metallic materials with nanocellulose and can be used as a base material or component in several applications. For example, hybrid composites are used in certain electronic devices such as solar cells, flexible displays and ultracapacitors where metals, e.g. Li, Mn, Ti, Zn, Ru, etc., are combined with nanocellulose papers, foils, sheets, tapes, etc. Hybrid nanocomposites containing cellulose and zinc oxide nanoparticles have excellent mechanical properties, UV barrier properties and antibacterial properties.
[0050]
[0056] In a particular aspect, the present invention relates to the use of a hybrid nanostructured composite in which the metal compound is zinc oxide, or a hybrid nanostructured composite of cellulose nanoparticles or zinc oxide nanoparticles, or a combination thereof, to replace titanium oxide as a white pigment in food or personal care products, or in paints, coatings and plastic articles.
[0051]
[0057] The present invention also relates to the use of the hybrid nanostructured composite of the present invention in the catalytic conversion of cellulose to performance chemicals, preferably to alcohols, sugars or acids, the acid being preferably acetic acid or lactic acid. The metal compounds in the hybrid nanostructured composite are preferably one or more selected from the group of ZnO, BaO, PbO, SnO, FeO, CaO, MgO and Al2O3. More preferably, the one or more metal compounds comprise ZnO. For example, a nanostructured hybrid composite comprising nanocellulose and 10-20 wt% ZnO may be heated at a temperature of 150-300°C, whereby the cellulose of the nanocellulose is converted to at least 25 wt% lactic acid relative to the weight of the nanostructured hybrid composite. The advantage of this method is that the ZnO nanoparticles are very well dispersed in the cellulose feedstock at the nanoscale, which reduces mass transfer limitations and times, resulting in higher yields with higher selectivity. Experimental Method XRD crystal type determination
[0058] The cellulose products obtained in the experiments are characterized using XRD. XRD measurements according to the method described by Z. Man, N. Muhammand, A. Sarwono, MA Bustam, M. Vignesh Kumar, S. Rafiq in J. Polym. Environ 19 (2011) 726-731: Preparation of cellulose nanocrystals using an ionic liquid. Crystalline forms I or II were identified by the peak positions, which were 22.6° in 2θ (
[0200] reflection) for form I and 20° and 22° in 2θ (
[0110] and
[0020] reflections) for form II. Prior to the XRD measurements, the product samples were dried at room temperature by vacuum drying. XRD crystallinity measurement
[0059] The crystallinity of the product (referred to in the literature as the crystallinity index) can be calculated according to Segal's formula: CrI=(I 002 -I am ) / I 002 (In the formula, I 002is the total intensity of the peak at 2θ of 22.6° for cellulose type I and 22° for cellulose type II, and I am is the intensity of the baseline at approximately 18° 2θ). XRD crystal size measurement
[0060] The cellulose crystal size was determined from the measured XRD using Scherrer's equation:
[0052]
number
[0053] where β is the crystallite size, λ is the wavelength of the incident X-rays, τ is the full width at half maximum (FWHM) of the XRD peak, and θ is the diffraction angle corresponding to the plane. Determination of cellulose product yield and cellulose hydrolysis
[0061] Soluble (poly)saccharides are mass balance % of (poly)saccharides = 1-M prec cel / M in cel (In the formula, M prec cel is the weight of dry microcellulose or nanocellulose obtained in the experiment, M in cel is the weight of dry cellulose placed in the reactor). The term (poly)sugars refers to sugars and polysaccharides, e.g., oligomeric sugars. Drying of the resulting cellulose product is performed according to NREL laboratory procedures, convection oven drying of the biomass at 45°C for 24-48 hours with periodic weight checks (usually every 3 hours) until the dry biomass weight does not change by more than 1% by weight per hour. Aspect ratio and crystal size measurements
[0062] The aspect ratio and crystal size of nanocellulose can be analyzed by scanning electron microscopy (SEM) or transmission electron microscopy. Materials used
[0063] The cellulose substrate in all experiments described below is cotton linter microcrystalline cellulose (MCC) ex-Sigma C6288. XRD characterization shows ±80% XRD-I type. ZnCl2 and ZnO were also obtained from Sigma. Experiment description Example 1 NC-II / Zn(OH) 2
[0064] A first solvent was prepared by adding 0.5 g of ZnO powder to 100 g of an aqueous solution of 60 wt% ZnCl2 in water and keeping the mixture under stirring (120 rpm / min) at room temperature overnight. The remaining unreacted ZnO solids were removed from the solution by filtration. 100 g of the resulting solvent was mixed with 5 g of cotton liner cellulose under stirring (480 rpm / min) and kept under stirring at room temperature for 30 min. The resulting cellulose type I crystals CI were separated from the solution by filtration through a glass filter, washed eight times with deionized water to remove ZnCl2, and dried under vacuum at room temperature.
[0054]
[0065] Subsequently, the highly crystalline cellulose type I crystal CI was contacted with a second solvent. The second solvent was a molten metal salt solvent prepared by mixing 0.5 g of ZnO powder (as a proton scavenger) with 100 g of 70-75 wt% ZnCl2 aqueous solution and keeping it under stirring at room temperature overnight. The remaining ZnO solid was removed from the solvent by filtration. 100 g of the second solvent was mixed with 5 g of cellulose type I crystal CI and stirred at room temperature for 30 min until the solution became clear.
[0055]
[0066] Cellulose was precipitated from the second solution by adding 225 g of deionized water to the solution under stirring to reduce the ZnCl2 concentration to 20 wt%. The sample was kept under stirring for 20 minutes to allow the cellulose nanocrystals to precipitate. The precipitation causes the solution to gel. The gel precipitate is filtered. The ratio of cellulose to ZnCl2 in the gel precipitate is 1:10 based on the dry solids weight.
[0056]
[0067] The gel contains highly pure nanocellulose (NC-II) with high crystallinity having XRD type II. XRD measurements of dried samples of this precipitate show that the cellulose XRD type obtained in the first dissolution step is converted in the second step to nanocellulose XRD type II with an XRD crystallinity of more than 80% and less than 5% by weight of saccharide monomers or oligomers formed.
[0057]
[0068] The gel precipitate was stirred at room temperature for 1 hour at a gel to clear water volume ratio of 1:8 until the product had a ZnCl content of about 10% by weight (cellulose to ZnCl 10:1 on a dry solids basis). room = 25° C. and wash twice with water. The resulting product is designated as Product 1-A.
[0058]
[0069] A quantity of 100 gr of this product 1-A is mixed with 0.1 gr of NaOH at a temperature T=25 °C, producing a cloudy gel-like solution which, after filtration, gives a wet precipitate containing a mixture of precipitated nanocellulose type II crystals and precipitated zinc hydroxide NC-II / Zn(OH)2. The amount of Zn(OH)2 in the hybrid complex can be optimized by using an excess of NaOH to ensure complete precipitation of Zn(OH)2, followed by washing off the residual NaOH. The solid coprecipitated NC-II / Zn(OH)2 is separated and washed twice with water (volume ratio of precipitate to water 1:8) to remove NaCl. The precipitate sample is then dried at 80 °C.
[0059] Example 2 NC-II / ZnO
[0070] In the preferred embodiment of Example 1 above, the resulting nanocellulose has high crystallinity and purity and decomposes at higher temperatures. It was found that the high crystallinity, high purity cellulose nanocrystals in the dry state have excellent thermal stability and resist decomposition even at temperatures above 200°C. This advantageous property can be exploited to thermally convert the hybrid nanostructured composite of the present invention at high temperatures. The precipitate sample NC-Zn(OH)2 obtained in Example 1 is heated at 200°C to convert Zn(OH)2 to ZnO. The final cellulose to ZnO dry weight ratio is 10:0.75 as determined by DTA and XRF.
[0060] Example 3 NC-II / LaCl 3
[0071] A quantity of 100 g of NC-II / ZnCl2 product 1-A was contacted with 1000 ml of LaCl3 solution (2 gr LaCl3 in 1000 ml water), thereby exchanging La and Zn to form a hybrid composition NC-II / LaCl3, with relative amounts of cellulose:LaCl3:ZnCl2 of 10:1:0.1.
[0061] Example 4 NC-II / La 2 O 3
[0072] The product obtained in Example B-1 is washed with NaOH to form La(OH)3, which is converted to La2O3 by dehydration at T = 200 °C under vacuum to produce the NC-II / La2O3 hybrid composite.
[0062] Example 5 NC-II / La 2 O 3 Whiteness test:
[0073] Nanocellulose NC was produced separately as described in Example 1, except that instead of adding Na-OH metal precipitant, the NC nanocrystals were washed, filtered and dried. ZnO nanoparticles were obtained commercially. The whiteness of the hybrid nanostructured composite NC-II / ZnO in Example 2 was compared with pure cellulose nanocrystals, ZnO nanoparticles and white paper. NC-II / ZnO in Example 2 appeared to have a higher whiteness than its constituents, as shown in the table below.
[0063] [Table 1]
[0064] Example 6 Catalytic conversion of cellulose
[0074] The nanostructured hybrid composite containing nanocellulose and 10 wt% ZnO was heated to 150–300 °C, thereby converting the cellulose into 25 wt% lactic acid with respect to the weight of the nanostructured hybrid composite.
Claims
1. A method for preparing a hybrid nanostructured composite material comprising cellulose nanocrystalline particles and metal compound nanoparticles, comprising: a) Virgin cellulose is treated with a metal ion M 1 A molten metal salt solvent M 1 - contacting the virgin cellulose with S to dissolve the virgin cellulose; b) Add a precipitating agent B to the molten metal salt solvent M 1 The metal ion M of -S 1 At least a part of the metal compound nanoparticles M 1- X or metal ion M 2 by contacting the metal ion M 1 At least a part of the metal ion M 2 and exchanged with metal compound M 2- precipitating the X nanoparticles, either directly or by adding a precipitating reagent B; c) adding an anti-solvent before, during or after step b) to precipitate the cellulose nanoparticles; d) isolating the co-precipitated cellulose and metal compound nanoparticles to obtain said hybrid nanostructured composite; e) optionally converting said metal compound in said hybrid nanostructured composite to another metal compound. A method comprising:
2. The molten metal salt M 1 -S is a zinc halide, preferably zinc chloride, zinc bromide or a hydrate thereof, more preferably ZnCl 2 Hydrate, most preferably ZnCl 2 . 4H 2 2. The method of claim 1, wherein the molten salt is preferably proton-free and preferably comprises a proton scavenger.
3. The molten metal salt solvent M 1 -S is the metal M of the molten salt solvent 1 Metal cation M other than 2 wherein the metal cation M 2 but preferably Li, Mn, Ti, Zn, Nd, Cd, Ag and Ru, most preferably TiCl 2 , MnCl 2 or LiCl 2 is one or more selected from the group consisting of 2 The amount of metal is M 1 and most preferably less than 20%, preferably less than 10 or 5 mol % of the amount of said molten metal salt solvent M 1 -S is ZnCl according to claim 2 2 hydrate, and the metal cation M 2 M 2 3. The method of claim 1 or 2, in a metal chloride.
4. In step a), the first solvent is 40-65 wt. % ZnCl in water. 2 contacting virgin cellulose with said first solvent, thereby dissolving the amorphous cellulose phase preferentially over the crystalline cellulose phase; isolating the optionally obtained crystalline cellulose having an XRDI-type structure; and dissolving the optionally isolated crystalline cellulose having an XRDI-type structure in water at a concentration of 65-90 wt. % ZnCl in water at a concentration higher than that of the first solvent. 2 to produce exfoliated cellulose having an XRD II-type structure, wherein said second solvent and preferably further said first solvent are free of a protonic acid, and preferably comprise a proton scavenger.
5. The precipitating reagent B is a base anion X, preferably containing hydroxy, carbonate or carboxylate, and reagent B is preferably NaOH, KOH, KHCO 3 , formate or acetate; and the precipitating reagent B is selected from the group consisting of a metal M 1 Nanoparticle precipitate M having 1 -X and / or metal M 2 M having 2 -X, and optionally the precipitating reagent B is a metal M 1 Metal ions other than M 2 or the metal M 1 Metal M 2 In exchange for metal M 2 -X precipitates, and the metal cation M 2 The method according to any one of claims 1 to 4, wherein is preferably one or more selected from the group consisting of Li, Mn, Ti, Nd, Cd, Ag and Ru.
6. The anti-solvent C is water, a ketone or an alcohol, preferably the salt concentration of the molten salt, preferably ZnCl 2 6. The method according to any one of claims 1 to 5, wherein the water is added in an amount to reduce the concentration to 10 to 30% by weight, preferably 15 to 25% by weight.
7. In step b), a precipitating agent B is added to the metal ions M 1 At least a part of the metal compound M 1- X nanoparticles, and then in step c) a poor solvent C is added to convert the metal compound M 1- or, preferably, the method comprises step a) followed by step c), then step b), which comprises adding an anti-solvent C to the cellulose solution obtained in step a) to form a gel of precipitated cellulose nanoparticles, optionally followed by separating and washing said gel to reduce the concentration of said metal salt in said molten salt solvent, followed in step b) by adding a precipitating reactant B to precipitate said metal ions M in the presence of said cellulose nanoparticles. 1 At least a part of the metal compound M 1- The method according to any one of claims 1 to 6, wherein the nanoparticles of X are converted into nanoparticles of X.
8. The molten metal salt solvent is ZnCl 2 . 4H 2 8. The method according to claim 7, wherein said precipitation reactant B is a hydroxide base resulting in a hybrid composite of cellulose and zinc hydroxide nanoparticles, and optionally treating the hybrid composite to convert the zinc hydroxide nanoparticles to zinc oxide nanoparticles by drying at elevated temperatures, preferably between 70-350°C, preferably between 80-300°C, even more preferably between 80-280°C.
9. Step a) is followed by step c) of adding an anti-solvent C to the cellulose solution obtained in step a) to form a gel of precipitated cellulose nanoparticles, optionally followed by separating and washing the gel to reduce the concentration of the metal salt in the molten salt solvent, and then purifying the solution with metal ions M 2 by contacting the metal ion M 1 At least a part of the metal ion M 2 with or after the addition of the precipitation reactant B, the metal compound nanoparticles M 2- The method according to any one of claims 1 to 8, wherein a precipitate of X is formed.
10. The method according to any one of claims 1 to 9, comprising a conversion step e) of converting said metal compounds in said hybrid nanostructured composite into another metal compound, preferably by pyrolysis, ion exchange, reduction or oxidation.
11. To link the cellulose nanoparticles, preferably glycerol, citrate, acetate or chitosan and an exchange metal M 2 of the group of organometallic compounds of the formula (I), preferably of the group of exchanged metals M 2 More preferably, the organometallic compounds of M 2 The method according to any one of claims 1 to 10, wherein an interconnecting agent selected from -acetate or -citrate is added, said interconnecting agent being preferably added in step b).
12. A hybrid nanostructured composite comprising cellulose nanocrystalline particles and metal compound nanoparticles obtainable by the method according to any one of claims 1 to 11, preferably comprising 2-20% by weight of metal compound relative to the total dry weight of the nanostructured composite, said hybrid nanostructured composite comprising cellulose nanoparticles, preferably having an X-ray diffraction (XRD) type II structure, preferably having an aspect ratio AR of at least 5, preferably at least 10, preferably having a minimum size of less than 60 nm, preferably less than 40 nm, more preferably less than 30 nm, and metal compound nanoparticles having an average particle size of less than 80 nm, preferably less than 60 nm, more preferably less than 40 nm, said cellulose and metal compound nanoparticles being homogeneously mixed at nanoscale.
13. 13. The hybrid nanostructure composite of claim 12, wherein said metal compound is zinc chloride, zinc hydroxide, zinc oxide or zinc carbonate, lanthanum chloride, lanthanum hydroxide, lanthanum oxide or lanthanum carbonate, lithium acetate.
14. Use of the hybrid nanostructured composite according to claim 12 or 13 for energy generation, in electronic devices, as pigments and / or pigment supports, as whitening agents or fillers in food or personal care products, as antimicrobial compounds, in antimicrobial clothing, in flexible and optically transparent paper, foil, tape or fabric, preferably the use of a hybrid nanostructured composite comprising zinc oxide as metal compound, optionally in combination with cellulose nanoparticles and / or zinc oxide nanoparticles, especially for replacing titanium oxide as a white pigment in food or personal care products, paints, coatings or plastic articles.
15. Use of the hybrid nanostructured composite according to claim 12 or 13 in the catalytic conversion of cellulose to performance chemicals, wherein the performance chemicals are preferably alcohols, sugars or acids, more preferably acetic acid or lactic acid, and the metal compounds in the hybrid nanostructured composite are preferably ZnO, BaO, PbO, SnO, FeO, CaO, MgO, Al 2 O 3 and more preferably, said one or more metal compounds comprise ZnO.